Are governance mode and foreign location choices independent?. (28th September 2021) - Leiblein, Michael J.; Larsen, Marcus M.; Pedersen, Torben
Abstract: Research Summary: This article explores the relationship between organizational governance and location choices. While the existing literature provides significant intuition regarding the factors that influence these choices, it often assumes that governance and location choice are independent from one another. This article tests the veracity of this assumption in the global semiconductor industry. We report evidence of significant correlations across choices regarding how to govern and where to locate production, evidence of a reciprocal relationship between governance and location choices, and evidence suggesting how interdependence between governance and location choices affects the stability of relationships highlighted by extant theories. We conclude with implications for future theoretical and empirical research based on the existence of these interdependent effects. Managerial Summary: Managers face difficult choices when deciding how to organize the performance of an activity. They must choose whether to outsource an activity by balancing the potential benefits of a supplier's lower costs or knowledge against the costs of diminished coordination and control. They must also choose where to perform an activity by considering the benefits of locally bound expertise as well as potential costs associated with cultural, legal, and social barriers. While prior research has often addressed these issues by assuming that these choices are independent, this paper demonstrates that governance and location choices are interdependent and that each choice reciprocally affects the other. It concludes by suggesting managers utilize an expanded governance‐location choice set when evaluating where and how to manage their core activities.